1999
DOI: 10.1046/j.1365-2672.1999.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation ofPseudomonas aeruginosaATCC 15442 to didecyldimethylammonium bromide induces changes in membrane fatty acid composition and in resistance of cells

Abstract: The role of membrane fatty acid composition in the resistance of Pseudomonas aeruginosa ATCC 15442 to the bactericidal activity of didecyldimethyl ammonium bromide (DDAB) was investigated. In this study, the strain was sub‐cultured in a medium with increasing DDAB concentrations. After adaptation, Ps. aeruginosa was able to grow until the DDAB concentration in the medium was about five times greater than the Minimal Inhibitory Concentration. Resistance of cells to the bactericidal activity of DDAB also increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
57
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 16 publications
6
57
1
3
Order By: Relevance
“…It is doubtful that true adaptation to TDA was seen in this study, as the tolerance was only 2-fold higher than that of nonadapted cells, whereas in the literature for quaternary ammonium compounds and the antimicrobial peptide cecropin B, it was reported to be many folds higher (23,31,43). The increased tolerance to TDA seen in this study could be the result of a phenotypic switch that is rapidly reversed after exposure to TDA.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…It is doubtful that true adaptation to TDA was seen in this study, as the tolerance was only 2-fold higher than that of nonadapted cells, whereas in the literature for quaternary ammonium compounds and the antimicrobial peptide cecropin B, it was reported to be many folds higher (23,31,43). The increased tolerance to TDA seen in this study could be the result of a phenotypic switch that is rapidly reversed after exposure to TDA.…”
Section: Discussioncontrasting
confidence: 44%
“…Another possibility is that TDA targets functions (genes) which are essential for bacterial survival and growth. A slow adaptation to gradually increasing concentrations of the drug has proven to be a successful way of obtaining stable strains with enhanced tolerance to an antimicrobial peptide and to biocides (24,31,35,47), but a similar approach was not successful in this study, as S. Typhimurium SL1344 immediately lost the gained tolerance. Previous studies showed a gradual deadaptation of the decreased sensitivity to different biocides (23,31,43,47); however, Sallum and Chen reported previously that tolerance to the antimicrobial peptide cecropin B was abolished after one passage in fresh medium without the peptide (43), as found in the present study with TDA and TDA extract.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, as with many other disinfectants, bacterial resistance to quaternary ammonium compounds (QACs) has recently caused serious problems. Pseudomonas aeruginosa isolates have frequently been found to be resistant to QACs (3,4,5,9,11,19,27,28). P. aeruginosa is ubiquitous in the environment and shows intrinsic resistance to high levels of QACs (18).…”
mentioning
confidence: 99%
“…11 Para P. aeruginosa adaptada em brometo de didecildimetil amônio, foi observado aumento nos ácidos graxos hidroxilados, sugerindo modificações também no lipídeo A, limitando a penetração do biocida pela membrana externa e mantendo a fluidez da membrana para a sobrevivência e crescimento da célula em presença do biocida. 8 Em B. cepacia, não foram verificadas alterações nas características nutricionais ou bioquímicas entre isolado clínico, resistente a 0,05% de cloreto de benzalcônio e com resistência induzida a 16% do biocida, observando-se apenas redução da virulência entre os três grupos. 3 As alterações na camada lipopolissacarídica foram observadas também em relação às bactérias resistentes a outros antimicrobianos.…”
Section: Discussionunclassified
“…Porém, são mais sensí-veis a outros compostos como o cloro e os compostos fenólicos, cujos modos de ação são completamente diferentes dos compostos de amônio quaternário. 5,8 Seis amostras, apesar de contaminadas, foram eficientes quando avaliadas utilizando-se bactérias-padrão para desinfetantes de uso domiciliar.…”
Section: Discussionunclassified